- #1

- 12

- 0

## Homework Statement

If the roots of the equation ax^2+bx+c=0 are α , β and if the roots of the equation a′x^2+b′x+c′=0 are (α +γ) , (β+γ) , prove that :

a′^2(b^2-4ac)=a^2+(b′^2-4a′c′)

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Radwa Kamal
- Start date

- #1

- 12

- 0

If the roots of the equation ax^2+bx+c=0 are α , β and if the roots of the equation a′x^2+b′x+c′=0 are (α +γ) , (β+γ) , prove that :

a′^2(b^2-4ac)=a^2+(b′^2-4a′c′)

- #2

Mark44

Mentor

- 36,011

- 7,941

Share: